1996
DOI: 10.1177/10454411960070020301
|View full text |Cite
|
Sign up to set email alerts
|

Current Concepts of Autoimmune Exocrinopathy: Immunologic Mechanisms in the Salivary Pathology of Sjögren's Syndrome

Abstract: Sjogren's syndrome is a systemic autoimmune disorder characterized by symptoms of oral and ocular dryness and a chronic, progressive loss of salivary and lacrimal function. The exocrine involvement is the result of a focal, peri-ductal mononuclear cell infiltrate and the subsequent loss of secretory epithelial cells. The mechanisms of this autoimmune exocrinopathy are not understood fully. Many recent investigations have described alterations in a number of immune mediators within the salivary glands. These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 90 publications
2
77
1
Order By: Relevance
“…In addition, it is well established that glandular atrophy is the long-term consequence of diminished function and that, in the elderly, it is possible to lose significant amounts of glandular tissue without affecting salivary flow (7)(8)(9). Overall, these findings strongly suggest that the lack of glandular function in many patients with SS is the result of a perturbation of acinar function, ultimately followed by atrophy (2)(3)(4)10).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, it is well established that glandular atrophy is the long-term consequence of diminished function and that, in the elderly, it is possible to lose significant amounts of glandular tissue without affecting salivary flow (7)(8)(9). Overall, these findings strongly suggest that the lack of glandular function in many patients with SS is the result of a perturbation of acinar function, ultimately followed by atrophy (2)(3)(4)10).…”
Section: Introductionmentioning
confidence: 86%
“…Although SS is classified as an autoimmune disease, no specific pathologic autoantibody has been found (3,13). However, data from recent studies have suggested that patients with primary SS and patients with secondary SS may have inhibitory autoantibodies directed against muscarinic receptors (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we asked whether the Th17/IL-23 system, involving both of the cytokines IL-23 and IL-17, is important in the development of Sjögren's syndrome (SS), an autoimmune disease characterized primarily by destruction of acinar tissue within the salivary and lacrimal glands (14)(15)(16)(17)(18)(19)(20)(21)(22)(23). Using an animal model of SS, we were able to investigate the temporal appearance of both IL-17-and IL-23-positive cells in the targeted glandular tissues, as well as the correlation between these cell populations and the presence of lymphocytic foci.…”
Section: Conclusion These Results Suggest That the Th17/ Il-23 Systementioning
confidence: 99%
“…Patients returned for oral (weeks 6,12,18,24) and physical (week 24) examinations, measurements of vital signs (weeks 6, 12, 18, 24), reviews of medical history, concomitant medications and adverse events (weeks 6, 12, 18, 24), hematology and blood chemistry tests (weeks 6, 24), and urinalysis (week 24). The safety variables assessed were divided into 7 main categories: 1) hematologic variables of red blood cells, hemoglobin, hematocrit, platelets, white blood cells, segmented neutrophils, lymphocytes, monocytes, eosinophils, and basophils; 2) body weight; 3) vital signs of temperature, heart rate, and blood pressure; 4) blood chemistry variables of glucose, sodium, potassium, chloride, blood urea nitrogen, creatinine, uric acid, phosphorus, calcium, cholesterol, triglycerides, protein, albumin, globulin, alkaline phosphatase, aspartate aminotransferase, alanine aminotransferase, gamma glutamyl transaminase, total bilirubin, and lactate dehydrogenase; 5) adverse events as reported by each subject; 6) urinalysis variables of pH, specific gravity, ketones, protein, glucose, bilirubin, blood, leukocytes, red blood cell count, and microscopic examination of urine; and 7) oral pathoses including fungal infections and episodes of salivary gland enlargement.…”
Section: Experimental Designmentioning
confidence: 99%
“…As the inflammatory disease progresses, the lymphocytic infiltration increases, leading to acinar gland degeneration, necrosis, and atrophy and decreasing exocrine function (6).…”
Section: Introductionmentioning
confidence: 99%